Analysis Of Event Quality Effect On Satisfaction And Behavioural Intentions Of The Ramayana Ballet Attendees (Case Study Of Puspo Budoyo Culture House) - Roozana Maria Ritonga (Jurnal Hospitality dan Pariwisata, 2019)
ABSTRACTEvent is becoming more increasingly important both socially and economically. Such growth has raised many questions concerning the quality of event and impact on satisfaction and behavioral intentions of attendees, however, few studies have examined the actual event quality of a cultural performance. With so many competitions in the event business, an event planner must increase the level of event quality. In additon to create satisfaction and revisit of attendees in the event, a highly quality of performance, employees and environment is recommended.This study examined the underlying structure of event quality and  impact between satisfaction and behavioural intentions. Three event quality dimensions (quality of event employees, quality of event environment, and event product quality) were analyzed with descriptive statistical method and regression analysis. This study is based on the cultural event of ‘Ramayana Ballet’ performance at Culture House of  Puspo Budoyo. The study therefore emphasizes event quality has a significant relationship between satisfaction and behavioural intentions, Furthermore, quality event employees, quality event environment and quality event product have significant impact on behavioral intentions. Keywords:  event quality, satisfaction, behavioral intentions